REPRESENTASI MAKNA “TAHIYYAH” Q.S AL-NISA’/4:86 DALAM KONTEKS PERDAMAIAN (ANALISIS SEMIOTIKA ROLAND BARTHES) - Muhaammad Syawal Rosyid Darman (Ushuluna: Jurnal Ilmu Ushuluddin, 2023)
This study discusses the use of the message of the meaning of tahiyah in the Qur'an with the semiotic analysis of Roland Barthes. In interpreting the word tahiyah, it doesn't just stop at the greeting. Furthermore, it works as the basic argument of Islam in creating peace between religious communities. This study uses the library method by collecting and processing data to translate into writing. The purpose of this research is to answer the question how is Roland Barthes' semiotic analysis on the meaning of the word tahiyah in QS al-Nisa '/4:86 and what is the message contained in the word. The results of this study indicate that the initial myth of the word tahiyah is the saying of hayaka Allah as a representation with fellow people in the Jahiliyah era. Then, the myth states by saying assalamualaikum wa rahmatullahi wa barakatuh. This is the identity of Muslims when greeting. Furthermore, the hidden message contained in the meaning of tahiyah is an expression of Islam in and maintaining peace between religious communities by respecting various differences as a sign.